Evaluation of Pump Capacity in Pancasila Pumping Station, Madiun City, East Java - Novi Andriany Teguh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Madiun River catchment area is widely known for flooding in the rainy season. There is an embankment built to prevent the flood from entering the city. With the existence of the embankment, pumps are required to discharge the rainwater from the urban drainage channel into the river. The pumps located in the pumping stations are spread across the Madiun City. Each pumping station has a different capacity and different catchment areas. Nevertheless, its capacity is not sufficient to discharge the water flowing from the drainage channel into the river without causing flood in the city. Hence, the evaluation of pump capacity is necessary. In this study, a case study of Pancasila Pumping Station as a pumping station with the biggest catchment area is taken. From the rainfall data, flood discharge in the inlet of the pumping station is calculated using a synthetic unit hydrograph of the Nakayasu method. The capacity of the pump will be evaluated using the resulted flood discharge, whether the capacity is sufficient or not. Furthermore, the necessary pump quantity, the pump capacity, the operational hours, and the volume storage needed will be calculated. The results are: maximum flood discharge with a return period of 10 years is 20.206 m³/s, the existing pump capacity is only 1,000 litre per second while the required pump capacity is 5 m³/s with the quantity of two units, both operated in the same time for 8 hours and one unit is operated for the ninth hour, equipped with a storage volume of 102,017 m³. Thus, the addition of pump capacity is necessary.